Correlations between omega-3 fatty acids and inflammatory/glial abnormalities: the involvement of the membrane and neurotransmitter dysfunction in schizophrenia - Zhang, Yongping; Yin, Jingwen; Yan, Haifeng; Yan, Ling; Li, Yuyu; Zhang, Cai; Li, Yajuan; Liu, Baiping; Lin, Juda; Zhang, Liqiang; Hu, Xueqiong; Song, Cai (Frontiers in Cellular Neuroscience, 2023)
Introduction Macrophages or T-lymphocytes triggered inflammation and, consequently, activated glial cells may contribute to neuroinflammation and neurotransmitter dysfunction in schizophrenia (SZ), while omega(n)-3 polyunsaturated fatty acids (PUFAs) can attenuate some SZ symptoms through anti-inflammatory effects. However, the correlations between macrophage/T-lymphocyte-produced cytokines and glia phenotypes, between inflammatory status and PUFAs composition, between cytokines and neurotransmitter function, and between n-3 PUFAs and neurotransmitter abnormality in SZ are unclear. Methods Changes in T-helper (h) patterns, peripheral macrophage/glial markers, PUFAs profile, membrane fluidity, and neurotransmitter functions were evaluated in SZ patients (n = 50) and healthy controls (n = 30) using ELISA, gas chromatography, fluorescence anisotropy techniques, and HPLC, respectively. Results Compared to the control, blood lymphocyte proliferation, the concentration of macrophage/microglia phenotype M1 markers, including cytokines IL-1β, TNF-α (Th1) and IL-6 (Th2), and astrocyte phenotype A1 marker S100β was significantly increased, while IL-17 and n-3 PUFAs contents, n-3/n-6 ratio, and membrane fluidity (FLU) were significantly decreased in SZ. Moreover, increased DA and HVA, decreased 5-HT and NE, and their metabolites appeared in SZ. Moreover, negative correlations between IL-6 and A2 marker Brain-Derived Neurotrophic Factor (BDNF) or n-3 PUFAs EPA and between IL-1β and FLU or 5HIAA, while positive correlations between EPA and 5-HIAA and between FLU and DHA were found in SZ. Discussion These findings showed (1) no clear Th pattern, but pro-inflammatory-dominant immunity occurred; (2) the pro-inflammatory pattern may result in the activated microglia M1 and astrocyte A1 phenotype; and (3) increased pro-inflammatory cytokines were related to decreased n-3 PUFA and decreased membrane fluidity and dysfunctional neurotransmitter systems in SZ.